Association between Aqueous Humor Cytokines and Structural Characteristics Based on Optical Coherence Tomography in Patients with Diabetic Macular Edema - Yan Chen; Bin Zheng; Haidong Li; Li Lin; Yuanyuan Fan; Mengai Wu (Journal of Ophthalmology)
Purpose. To investigate the relationship between aqueous humor cytokines and structural characteristics based on optical coherence tomography (OCT) in patients with diabetic macular edema (DME). Methods. Forty eyes of 28 patients with DME diagnosed in the Affiliated Eye Hospital of Wenzhou Medical University at Hangzhou were included. All patients collected aqueous humor during anti-VEGF treatment, and the IL-6, IL-8, IL-10, VEGF, VCAM-1, ICAM-1, TGF-β1, FGF, and MCP-1 concentrations were detected. OCT examination was performed before anti-VEGF treatment and 1 month after anti-VEGF operation. Central macular thickness (CMT), macular volume (MV), choroidal thickness (CT), and the number of hyperreflective foci (HRF) were obtained for analysis. Each eye was determined whether there is subretinal effusion (SRD), cystoid macular edema (CME), and diffuse retinal thickening (DRT). Results. The levels of IL-6 and FGF in DME patients with SRD were significantly higher than those without SRD (all P<0.05). The level of VEGF in DME patients with CME was significantly higher than that in DME patients without CME (P=0.005); IL-6, TGF-β1, and MCP-1 were significantly higher in DME patients with DRT than that without DRT (all P<0.05). There was no significant correlation between aqueous humor cytokines and retinal thickness and retinal volume. However, the thinner the CT, the higher the level of aqueous humor cytokines IL-6 (r = −0.313, P=0.049) and FGF (r = −0.361, P=0.022). A multivariate linear regression analysis showed that IL-6 was significantly correlated with CT (P=0.002) and SRD (P=0.017), FGF was also significantly correlated with CT (P=0.002) and SRD (P=0.005), and TGF-β1 was correlated with triglycerides (P=0.030) and HRF (P=0.021). Conclusion. DME patients with significant macular cystoid edema changes may be related to high VEGF concentrations and thin CT; meanwhile, the presence of SRD or a high number of HRF on OCT macular scans in DME patients may indicate high levels of intraocular inflammatory factors. Thus, OCT morphology characteristics to some extent reflect intraocular inflammatory factors and VEGF levels and may guide treatment alternatives.